Structural and electrical characterisation of silicon and other semiconducting nanoparticle networks for use in sensor and photovoltaic applications - Setshedi, R K (Department of Physics, 2016)
A recent study investigated the feasibility of a sequential heap leach in low grade Platreef ore in order to recover PGMs (Platinum Group Metals), by a pure hydrometallurgical route. This method comprised of two stages, an initial thermophile bioleach stage to extract base metals followed by a cyanide leach to recover precious metals, PGMs. The study conducted assessed the possibility of excluding costly stages such as concentration by flotation, smelting and pressure leaching by directly leaching low grade Platreef ore. The findings showed successful base metal recoveries; however, the production of thiocyanate during the cyanide leach raised concerns in terms of significant cyanide loss but also whether thiocyanate contributed positively to PGM recovery. Cyanide present in processing liquors is known to react with various sulphur species, depending on the mineralogy of the ore and the chemical constituents within the system. These interactions between cyanide and reduced sulphur species, generated through incomplete oxidation of sulphidic ores, are primarily responsible for thiocyanate formation. In addition, thiocyanate generated during these processes has been identified to mobilise both base metals and precious metals, forming highly stable and soluble complexes with precious metals. Recent work in the field has shown pronounced recoveries during thiocyanate leaching of PGMs from virgin catalytic converters. However, a significant portion of previous research work has focused on metallic gold, with a lack of knowledge regarding thiocyanate leaching of PGMs associated with sulphidic minerals. This study investigates the chemical kinetics of thiocyanate formation in a thiosulphate, sulphite and polysulphide system in the presence of cyanide. The initial rate kinetics of thiocyanate formation, explored in homogenous systems, displayed fairly rapid reaction kinetics in the cyanide-polysulphide system relative to the thiosulphate-cyanide system. Additionally, sulphite exhibited a minor affinity for cyanide as no measurable concentration of thiocyanate was observed. This serves to verify that polysulphides generated during incomplete oxidation of sulphidic minerals are most likely responsible for SCN- formation and not the direct interactions between sulphidic minerals and cyanide. Further, this research is an initial attempt to investigate the effectiveness of thiocyanate leaching in Pt and Pd containing minerals under varied conditions. In the process, it seeks to establish whether thiocyanate and cyanide act synergistically to promote the dissolution of Pt and Pd. Preliminary test work carried out on Platreef concentrate demonstrated that the presence of base metals significantly limited the concentration of free thiocyanate available for leaching. From the results observed, Fe (under acidic conditions) and Ni displayed a strong affinity for thiocyanate, attributed to the formation of highly stable complexes. However, Cu demonstrated a negligible effect on thiocyanate consumption, forming an insoluble salt complex, CuSCN(s).